2010
DOI: 10.4103/0378-6323.66593
|View full text |Cite
|
Sign up to set email alerts
|

Tophi as first manifestation of gout

Abstract: Chronic tophaceous gout classically occurs after 10 years or more of recurrent polyarticular gout. However, tophi can also occur as first sign of the disorder. Here we report a 20-year-old male presenting with multiple subcutaneous nodules on bilateral feet and toes, left palm, right elbow, helix of left ear since last one and half year prior to any other manifestation of gout. He was having mild intermittent arthritis since last six months. Fine Needle Aspiration Cytology of one tophus showed monosodium urate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 9 publications
3
24
0
Order By: Relevance
“…[2], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21 ], [22], [23] Details of these are shown in ( …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2], [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21 ], [22], [23] Details of these are shown in ( …”
Section: Discussionmentioning
confidence: 99%
“…Bothale et al [13] 2012 1 Great toe Rheumatoid arthritis Koley et al [14] 2010 1 Bilateral feet and toes, left palm, right elbow, helix of left ear Arthritis Gupta et al [15] 2009 1 Left elbow joint and near the lateral malleolus of the left foot…”
Section: Not Givenmentioning
confidence: 99%
“…1 Although gouty tophi are seen in chronic disease, in a few conditions tophi may be the first sign of the disorder. 2,3 Hyperuricemia is a common complication in organ transplant recipients and frequently is associated with chronic cyclosporine immunosuppressive therapy. 4,5 Kidney transplant recipients are prone to develop post-transplant hyperuricemia.…”
Section: Discussionmentioning
confidence: 99%
“…Photomicrograph of another section had been stained by de Galantha's method for demonstration of monosodium urate crystals ( Figure 2). subcutaneous nodules, knee, acromioclavicular joint and axial skeleton [3][4][5][6][7][8][9][10][11][12][13][14]. A recent study suggested that the frequency of axial involvement may be as high as 14% in patients with clinical or crystal-proven gout [15].…”
Section: Case Reportmentioning
confidence: 99%
“…Chronic tophaceous gout classically occurs after 10 years or more of recurrent polyarticular gout. However, demonstrating tophi as the initial clinical presentation of gout is very rare [8]. Subcutaneous tophi generally occurs as a late clinical outcome and typically located in the peripheral joints of the hand or foot [10].…”
Section: Case Reportmentioning
confidence: 99%